The impact of depression and cardiovascular disease on fall risk in type 2 diabetes mellitus: a gender and sleep status analysis - Li, Kehua; Chen, Xue; Chen, Lang; Liang, Dianyin (Frontiers in Public Health, 2025)
BackgroundThis study aims to examine the combined effects of depressive symptoms (DS) and cardiovascular disease (CVD) on fall risk in patients with type 2 diabetes mellitus (T2DM), as well as evaluating the potential moderating effects of sleep status and gender.MethodsThis study analyzed 941 participants from the China Health and Retirement Longitudinal Study (CHARLS). Participants were divided into four groups: those with both depressive symptoms and CVD (DS+/CVD+), those with only depressive symptoms (DS+/CVD−), those with only CVD (DS−/CVD+), and those with neither depressive symptoms nor CVD (DS−/CVD−). Additionally, stratified analyses were conducted to differentiate participants based on sleep statuses and gender.ResultsIn the absence of potential confounding variables, the phenotypes DS+/CVD+, DS+/CVD−, and DS−/CVD+ were each independently linked to a higher fall risk relative to the reference category DS−/CVD− (RR = 1.96, 95% CI: 1.25–3.07; RR = 1.92, 95% CI: 1.29–2.87; RR = 1.58, 95% CI: 1.03–2.42, respectively). Specifically, within the sleep sufficiency group, the DS+/CVD+, DS+/CVD−, and DS−/CVD+ phenotypes exhibited a significantly elevated risk of falls relative to the DS−/CVD− phenotype (RR = 2.23, 95% CI: 1.22–4.05; RR = 2.02, 95% CI: 1.19–3.43; RR = 1.73, 95% CI: 1.02–2.93, respectively). After adjusting for confounding variables, Males with DS−/CVD+ phenotypes are significantly more likely to fall (RR = 2.04, 95% CI: 1.04–3.98). In contrast, the DS+/CVD+ and DS+/CVD− phenotypes are linked to a heightened risk of falls in females, with relative risk of 1.79 (95% CI: 1.04–3.09) and 1.82 (95% CI: 1.11–2.98), respectively. Furthermore, there was no evidence of an additive interaction between depression and CVD in relation to fall risk among patients with T2DM (p > 0.05).ConclusionThe co-occurrence of depression and CVD significantly elevates the risk of falls in diabetic patients. It is recommended that female patients prioritize the prevention and management of depression, whereas male patients should focus on the prevention and management of cardiovascular diseases. Additionally, ensuring adequate sleep is essential for all patients.